Determinant of Murabaha financing in Indonesian Sharia banking: The ARDL and NARDL approach - Widarjono, Agus; Misanam, Munrokhim (Journal of Islamic Economics Lariba, 2023)
IntroductionMurabaha financing accounts for the largest portion of Sharia bank financing, and many previous studies have analyzed this topic using symmetric impact. However, studies using the asymmetric link, a common phenomenon in economic theory, are limited.ObjectivesThis study explores the determinants of Murabaha financing with symmetric and asymmetric approaches. MethodThe explanatory variables are the bank-specific variables in the form of the Murabaha financing rate, the cost of borrowing money, and the macroeconomic conditions in the form of the Industrial Production Index, which is a proxy of domestic output. The period of study is from 2010 to 2021 using monthly data. The method is Autoregressive distributed lag (ARDL) for symmetric analysis and non-linear ARDL (NARDL) for asymmetric analysis.ResultsThe symmetric effect method indicates that the Murabaha financing rate negatively affects Murabaha financing, but the Industrial Production Index has no effect on Murabaha financing. The asymmetric effect method suggests that the Murabaha financing rate and Industrial Production Index asymmetrically affect Murabaha financing. ImplicationsMurabaha financing will experience a drastic fall if there is a rise in the Murabaha financing rate, but a fall in the Murabaha financing rate will not have an impact on an increase in Murabaha financing. Economic upturns boost Murabaha financing, but economic downturns have no impact on Murabaha financing.Originality/NoveltyThe main contribution of our research is evidence of the asymmetric response of Murabaha financing to bank-specific variables as well as macroeconomic conditions in which Sharia banks are resilient to the business cycle.